KINERJA POS LINTAS BATAS NEGARA (PLBN) TERPADU WINI DI KAWASAN PERBATASAN RI - RDTL KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA TIMUR - Gradiana Tefa; Florianus P. Thaal (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
State border management is an important aspect in maintaining the integrity and sovereignty of a country. The start of the Asean Economic Community (AEC) program in 2015 among Southeast Asian countries in order to improve the economy, the border region became a strategic place that was the gateway to various cooperation activities between countries. To improve crossborder services between countries, the Government issued INPRES No. 6 of 2016 concerning the Development of 7 Cross-border State Posts. One of the construction of the State Border Crossing Post is located in North Insana District, North Central Timor Regency, East Nusa TenggaraProvince. This study aims to determine the performance of Integrated Wini Cross-border Post (PLBN) in cross-border service activities in the RI-RDTL Border Region of North Central Timor Regency, East Nusa Tenggara Province. This research uses a qualitative research design with a descriptive approach. Informants in the study were determined by purposive sampling and incidental sampling techniques. Data collected by interview, observation and documentation techniques. And in analyzing data using miles and huberman models, namely data reduction, data displays and drawing / verification conclusions. The results showed that the performanceof Pos Lintas Batas Negara Terpini wini in cross-border service activities was not optimal. This is influenced by the inhibiting factors, among others, limited personel resources, limited facilities and infrastructure, weak coordination between elements of CIQ, difficulties in licensing trade documents, and lack of understanding of the community. Based on the results of the analysis, the authors suggest that PLBN Managers improve coordination between elements of CIQ, provide socialization to the community, improve service facilities and infrastructure, facilitate licensing of trade documents to increase recruitment of CIQ employees. Keywords: Performance; Border; PLBN